(untitled) (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2025)
First-year university students often face significant challenges during their transition from high school to higher education, including increased academic demands and decreased external structure. This literature study analyzes previous research on how coping mechanisms, academic adjustment, and social support influence academic procrastination among first-year students. The goal is to provide a theoretical foundation for understanding how these three variables interact and contribute to procrastination behavior, while also offering insights for the development of effective intervention strategies. Academic procrastination refers to the intentional delay in completing academic tasks despite awareness of its negative consequences. Utilizing a literature review method, this article examines how adaptive coping strategies (e.g., problem-focused coping), effective academic adjustment, and strong social support systems can help reduce procrastination. The study also highlights the significant role of social support—emotional, informational, or instrumental—as a key mediator that strengthens adaptive coping strategies and fosters better academic adjustment. Furthermore, social support—whether emotional, informational, or instrumental—acts as a mediating factor that reinforces positive coping and adjustment. The study emphasizes the importance of integrated approaches that promote adaptive coping, academic adjustment, and a strong support system, particularly during the critical transition into university life, to improve students’ academic performance and overall well-being.